Evaluating and Engaging: Using Participatory Video With Kenyan Secondary School Students to Explore Engagement With Health Research - Davies, Alun; High, Chris; Mwangome, Nancy; Hanlin, Rebecca; Jones, Caroline (Frontiers in Public Health, 2022)
Background: The growing ethical requirement to engage communities with health research has yielded diversification in approaches and targeted audiences. Conventional approaches like community ‘town-hall meetings’, laboratory open-days and focus group discussions, have evolved into new methods and audiences such as community drama and school engagement with health research (SEHR) involving learning interactions between researchers and school students. While engagement practices are diversifying, evaluations of these initiatives are rare in Low- and Middle-Income Countries (LMIC). This article focuses on the use of Participatory Video (PV) to explore the influence of the KEMRI-Wellcome Trust Research Programme’s (KWTRP) School Engagement Programme (SEP) on the views and understandings of science and research among Kenyan state secondary school students. Methods: Twelve male and twelve female students from four coeducational schools were provided with film-making kits (1 per school), and a one-day PV training workshop. They prepared 22 short films over eight weeks depicting their experiences and views of research and engagement and conveying their career aspirations. Schools were selected based on prior SEP participation; two schools having experienced different engagement approaches, and the others with no prior school engagement. Study data comprised footage and participant observation notes. Results: PV provided an opportunity to simultaneously engage and evaluate to inform practice. Through student-led filmmaking, PV stimulated conversations with students about research and engagement, enabling them to share their views in a way they felt was appropriate. These interactions offered an understanding of student gains from engagement, the depth of interaction required to address perceptions held about research and the potential unintended consequences of engagement. PV also provided insights into the context and complexity of life in which engagement is situated. Understanding this context is important because of its potential influence on participation in engagement activities. We draw on these insights to make two recommendations for school engagement practice. First is that PV can provide an enjoyable and insightful means of combining engagement with evaluation. Second, given that time for SEHR is competed for against other important curricular and extracurricular activities, SEHR practitioners must ensure that activities are as beneficial and enjoyable as possible to students.